The Implementation of Project Based Learning Through Two-Stay Two Stray Technique to Promote Students Creative Thinking Skill In Procedure Text - Opan Siroj; Sri Wahyuni (Green Publisher Indonesia, 2026)
Students’ creative thinking skills were in the low category, as they were only able to meet the indicators of fluency and flexibility, while the indicators of originality and elaboration still needed improvement. This study aims to analyze the implementation of the Project Based Learning (PjBL) model through the Two-Stay Two-Stray Technique to promote creative thinking skills in procedure text material. The research method used was a mixed-method approach with a one-group pre-test–post-test design. The research sample consisted of 30 ninth-grade junior high school students. The instruments used included a creative thinking skill test in the form of essay questions and a student response questionnaire. Data analysis involved a paired sample t-test to compare students’ mean scores before and after the treatment, followed by an N-Gain analysis with the assistance of SPSS version 25. The results of the study showed an increase in the average score of creative thinking skills from the “fair” category to the “excellent” category, with an N-Gain score in the medium category (0.673). The creative thinking indicators that showed improvement with a high N-Gain category were fluency, flexibility, and originality, whereas the elaboration indicator obtained a low N-Gain category. The average percentage of students’ responses to the learning ranged between 87%–89%, which fell into the “excellent” criteria. Based on these findings, it can be concluded that the implementation of the PjBL model through the Two-Stay Two-Stray Technique was able to equip students with creative thinking skills in procedure text material, achieving an N-Gain category of medium.